Slope aspect effects on plant community characteristics and soil properties of alpine meadows on Eastern Qinghai-Tibetan plateau. (October 2022) - Zhang, Qi-peng; Fang, Ru-yao; Deng, Cui-yan; Zhao, Hong-juan; Shen, Meng-Han; Wang, Qian
Highlights: The slope aspect has a significant effect on the characteristics of plant communities. Plant functional groups and plant diversity showed consistent trend changes at the slope aspect transition from the north to south slope. The characteristics of plant functional groups varied with the physical and chemical properties of the soil. Plant diversity significantly correlated with soil pH and SWC (P < 0.05) but not with the other soil physical and chemical properties (P > 0.05). Abstract: Slope aspect has an important impact on vegetation morphology, structure, and spatial distribution. However, the effects of different slope aspects on the characteristics of plant communities, and soil physical and chemical properties in alpine meadows remains unclear. Here, we selected the gully hillsides of Dangzhou, distributed along the eastern border of the Qinghai-Tibetan plateau, as the study object. Based on variance and correlation analysis, we determined the following results. The slope aspect has a significant effect on the characteristics of plant communities. Significant differences in plant functional groups and plant diversity among different slope aspects in alpine meadows were found (p-value < 0.05). Plant functional groups and plant diversity showed consistent trend changes at the slope aspect transition from the north to south slope. The slope aspect affected the physical and chemical properties of the soil. With the slope aspect varied from North to South, pH, ST (soil temperature), and STP (soil total phosphorus) increased, whereas soil organic matter (SOM), soil total potassium, soil water content (SWC), and soil total nitrogen showed a decreasing trend (p-value < 0.05). The characteristics of plant functional groups varied with the physical and chemical properties of the soil. A significant correlation between plant functional groups and soil pH, SOM, and SWC was observed (p-value < 0.05). Plant diversity significantly correlated with soil pH and SWC (p-value < 0.05) but not with the other soil physical and chemical properties (p-value > 0.05). Our findings may provide a scientific basis for the sustainable use of alpine meadows and the evaluation of ecosystem services in alpine meadows.